2018
DOI: 10.2903/sp.efsa.2018.en-1521
|View full text |Cite
|
Sign up to set email alerts
|

Understanding ASF spread and emergency control concepts in wild boar populations using individual‐based modelling and spatio‐temporal surveillance data

Abstract: African swine fever (ASF) infection is circulating in Eurasia since a decade within wild boar populations without a demonstrated vector host. Further the infection was recurrently translocated by spatio‐temporal dynamics that is incompatible with wild boar movement characteristics. Management actions are required in areas affected by ASF. Control measures address areas with recent focal introduction and areas with ASF circulating several seasons or endemic occurrence. In view of acknowledged gaps in understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 22 publications
4
77
0
1
Order By: Relevance
“…Our estimates, which are for spread by wild boar movement only, match the lower bounds of these statistical analyses. Overall, our findings regarding boar movement and ASF spread are in line with previous work, suggesting that wild boar movements have only a small role to play in ASF transmission (Podgórski and Śmietanka 2018) although this can depend on geographical location (Iglesias et al 2018), and the fact that transmission by wild boar is driven principally by boar carcasses (Figure 3, Lange et al (2018)).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our estimates, which are for spread by wild boar movement only, match the lower bounds of these statistical analyses. Overall, our findings regarding boar movement and ASF spread are in line with previous work, suggesting that wild boar movements have only a small role to play in ASF transmission (Podgórski and Śmietanka 2018) although this can depend on geographical location (Iglesias et al 2018), and the fact that transmission by wild boar is driven principally by boar carcasses (Figure 3, Lange et al (2018)).…”
Section: Discussionsupporting
confidence: 91%
“…However, as already stated, many of the recent countries with new incursions have implemented a combined strategy of 3 control strategies (fencing, hunting and carcass removal) in different zones. We did not combine intervention strategies, as our focus was on the movement model rather than the control strategies, however, Lange et al (2018) considered various strategies combining zoning, hunting, carcass removal and fencing. Similar to our control strategy of fences with 10km width, they found that fencing may be ineffective if based on locations of reported cases and not on locations of actual infected boar, but in general they found fencing to be a less successful strategy and instead focussed on combining intensive hunting with carcass removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effort per campaign is adjusted to achieve in summary the annual efficacy of depopulation per cent. NB: The culling measures in the core + buffer zone did not alter over all simulations and were set at 90% as after 26 weeks waiting time Uncertainty discussion: Thinking of culling as a large-scale disturbance effect may create substantial uncertainty to the result (see as partial solution in Lange et al, 2018).…”
Section: Alternative Timing Of Hunting Activities Over the Yearmentioning
confidence: 99%
“…Both (B) and (C) cross-tabulate column-wise different permeability of the fence (left 0% wild boar proof; 5%; middle 10%; 50%; right 90% fence nearly absent) vs row-wise different carcass detection rates (top 1%; 10%; middle 20%; 40%; bottom 80%). Zoning is based on perfect knowledge about infectious carcass distribution at the moment of zoning (results for 10% chance of carcass detection, see Lange et al, 2018). Independent of the size of the buffer zone, and because the core + buffer zones are subject to a hunting ban prior to final culling, ASF will spread into the buffer zone and may subsequently break out (i.e.…”
Section: Adding Fences Around the Core Zonementioning
confidence: 99%